'Educate, Empower and Inspire': An Evaluation of a Preventative Service for Young People at Risk of Sexual Exploitation. (12th February 2021) - Unwin, Peter; Jones, Alexandra
Abstract : Key Practitioner Messages: Young people at risk of child sexual exploitation (CSE) value peer mentoring and will respond to services that they regard as authentic, consistent and tailored to their needs. Practitioners should always endeavour to prioritise the voices of young people - they are articulate about CSE. Arts‐based projects should be given fuller consideration as a potentially effective vehicle for building resilience and combatting the CSE threat.